Determinants of Trust in Business-to-Business Relationships: ‎The Role of Relationship Quality, Service Quality, and ‎Communication - Angeli Margaretha; Yudi Nur Supriadi (Yayasan Darussalam Bengkulu, 2026)
This study aims to examine the determinants of trust in business-to-business (B2B) relationships and develop an integrative conceptual framework linking relationship quality, service quality, and communication with trust. Previous studies analyzed these determinants separately, limiting understanding of their combined effect on inter-organizational collaboration. A systematic literature review following the PRISMA framework was conducted using Scopus-indexed journals (2021–2026). From 620 records, 37 articles met eligibility criteria, and 30 were synthesized through thematic analysis. Findings show that relationship quality is the strongest predictor of trust, encompassing satisfaction, commitment, continuity, and conflict reduction. Service quality enhances trust through reliability, responsiveness, efficiency, and partner competence. Communication acts as a moderator by increasing transparency, reducing information asymmetry, clarifying expectations, and facilitating knowledge sharing. The proposed conceptual model positions relationship quality and service quality as antecedents of trust, with communication strengthening and moderating trust formation. Theoretically, the study frames trust as a dynamic relational capability shaped by operational performance, relational experience, and information exchange. Practically, it suggests firms should manage trust strategically through consistent service delivery, long-term relationship investment, and structured, transparent communication. Limitations include reliance on literature-based synthesis; future research should empirically test the model across diverse B2B contexts.